The Role of Intelligent Transport Systems in Providing Transport Services to The Population: Economic Efficiency - F.A. Omonov (European Science Publishing, 2023)
In this article, the introduction of modern technologies of intelligent transport systems in urban public transport and its impact on the level of public transport services in Tashkent city and the efficiency of urban public transport were studied. Issues related to providing the population with a cheap, convenient and efficient public transport system, improving the quality of the transport services provided to them were thoroughly studied, relevant conclusions and suggestions were given.
Keywords: intelligent transportation systems, public transport, traffic flow, meters, cost-effectiveness, traffic lights, passenger.